Behavioral study of concrete composite with mixture of fly ash and concrete sludge aggregate - Mohd Shakirim Harith (School of Environmental Engineering, University Malaysia Perlis, 2013)
The alternative to replace partial replacement of cement and aggregate are by using the fly ash and concrete sludge aggregate. From the research, fly ash and concrete sludge aggregate needs space of landfill to dispose off whereas the population density is high and expensive price